Pentingnya peran logo dalam membangun sebuah brand - Hitami, Akhmad (Maliki Interdisciplinary Journal, 2023)
A brand is an invaluable asset in modern business, and the logo serves as a primary visual element in shaping the brand’s identity. The logo is a graphic symbol that reflects the character, values, and essence of the brand. This article discusses the significance of the logo’s role in building the brand identity of an entity or company. The writing describes various types of logos, including Logotype, Logomark, and Combination Mark, and analyzes well-known company logos such as Amazon, Sony VAIO, and FedEx to illustrate how logos can create an emotional connection with customers, establish brand identity, and provide a professional visual impression. However, there is a phenomenon where many logos are created without careful planning, such as in logo design contests or cheap logo creation services, resulting in shallow logos that often do not adequately reflect the brand’s character. The lack of awareness of the logo’s role in building a brand is evident among entrepreneurs and designers. The author aims to encourage steps to enhance understanding of the importance of building a brand and the role of the logo in this process through seminars, workshops, and campaigns. Awareness of the importance of investing in a brand and a well-designed logo will have a positive impact on building a strong and sustainable brand.